The association between visual display terminal use and dry eye: a review. Issue 4 (25th October 2021) - Fjærvoll, Haakon; Fjærvoll, Ketil; Magno, Morten; Moschowits, Emily; Vehof, Jelle; Dartt, Darlene A.; Utheim, Tor P.
Abstract: Background: Dry eye disease (DED) is a multifactorial disease of the tear film and ocular surface. It causes ocular symptoms, reduced quality of life and a considerable economic burden on society. Prolonged use of visual display terminals (VDTs) has been suggested as an important risk factor for DED. Purpose: This review aims to study the association between DED and VDT use with an emphasis on the prevalence of DED among VDT users and harmful daily duration of VDT use. Methods: A PubMed search was conducted and yielded 57 relevant articles based on a set of inclusion and exclusion criteria. The studies were subclassified according to study design. Results: The far majority of the studies showed an association between VDT use and DED or DED‐related signs and symptoms. The prevalence of definite or probable DED in VDT and office workers ranged from 26% to 70%, with as few as 1–2 hr of VDT exposure per day being associated with DED. Conclusion: VDT use is strongly associated with DED. VDT‐associated DED is prevalent, but the exact prevalence needs to be further elucidated using standardized DED diagnosis criteria. Furthermore, a safe lower limit of daily VDT use has yet to be established. More research is needed on the effect of digitalization and digital transformation, which are particularly high during the time of the COVID‐19 pandemic.